2005
DOI: 10.1111/j.1469-8749.2005.tb01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in children and adolescents with disabilities

Abstract: This review presents a discussion of the sexual development of children and adolescents with disabilities, described in the framework of body structure and function, individual activities, and societal perspectives presented in the World Health Organization's International Classification of Functioning, Disability and Health. Issues of sexual development, gynecological care and contraception, sexual functioning, societal barriers, sexual victimization, and sexuality education are presented. Overall, adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 24 publications
1
27
0
2
Order By: Relevance
“…Mack et al 2010), which indicated that having ASD is a unique contributing factor to peer relationship problems. Difficulties in this area may become increasingly problematic when reaching adolescence (Murphy and Young 2005), as peer relationships become increasingly important (La Greca and Harrison 2005) and complex (Laugeson et al 2012). The difficulties with intimacy as well as rejection by peers which adolescents with ASD reported may lead to loneliness, social anxiety and depression (Eussen 2015; La Greca and Harrison 2005) as well as frustration (Hellemans et al 2010) which have been related to problems such as anxiety and sexual delinquency (Marshall 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mack et al 2010), which indicated that having ASD is a unique contributing factor to peer relationship problems. Difficulties in this area may become increasingly problematic when reaching adolescence (Murphy and Young 2005), as peer relationships become increasingly important (La Greca and Harrison 2005) and complex (Laugeson et al 2012). The difficulties with intimacy as well as rejection by peers which adolescents with ASD reported may lead to loneliness, social anxiety and depression (Eussen 2015; La Greca and Harrison 2005) as well as frustration (Hellemans et al 2010) which have been related to problems such as anxiety and sexual delinquency (Marshall 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (2006) has identified that adequate sex education is a right of every individual, regardless of disability, and that without it, the physical and emotional health of the adolescent is at risk (Murphy and Young, 2005). Yet the questions and concerns being expressed by participants in this study indicate that sex education can be inaccessible to young people with special needs, and they do not seem to receive adequate specific information regarding their sexual health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…People with ID have the same sexual desires and needs as those without disability (Borawska-Charko, Rohleder & Finlay 2016), yet their sexuality has been marked by a number of myths, stereotypes and false beliefs that despite lacking any scientific evidence to support them, have fostered negative attitudes towards this social group and curbed their right to achieve a free and adequate expression of their sexuality (Franco, Cardoso & Neto 2012;Olavarrieta et al 2013). A large part of society has generally considered them to be asexual beings that are unable to make appropriate decisions about their sexuality due to the fact that they need support, protection or supervision (Murphy & Young 2005;Swango-Wilson 2009). As a result, they have often been sterilised, repressed or institutionalised with the aim of avoiding sexual relationships and preventing pregnancies (McDaniels & Fleming 2016).…”
Section: Introductionmentioning
confidence: 99%